Prediction of secondary metabolites in hydroponically produced tomatoes: multivariate influence of abiotic climatic factors as well as photosynthesis and transpiration rates - Grigorij Devadze; Dennis Dannehl; Annika Nerlich; Uwe Schmidt; Stefan Streif; Stefan Streif (Frontiers in Plant Science)
This is the first study who presents an approach to predict secondary metabolites content in tomatoes using multivariate time series classification of greenhouse sensor data, which includes climatic conditions as well as photosynthesis and transpiration rates. The aim was to find the necessary conditions in a greenhouse to determine the maximum content of secondary metabolites, as higher levels in fruits can promote human health. For this, we defined multiple classification tasks and derived suitable classification function. Cross-validated high accuracy results demonstrate the effectiveness of the approach. Considering a period of three weeks, we found that PPFD levels between 396.0 μmol/m2s and 511.2 μmol/m2s as well as transpiration rates ranging from 4.4 mg H2O/m2s to 7.47 mg H2O/m2s were observed as optimal for the contents of beta carotene, lutein, and lycopene. Optimal contents for naringenin and phloretin diglucoside can be achieved at lower PPFD ranges from 229.4 μmol/m2s to 431.2 μmol/m2s and from 35.76 μmol/m2s to 262.28 μmol/m2s and at lower transpiration rates from 4.71 to 6.47 mg H2O/m2s and from 3.04 to 4.26 mg H2O/m2s, respectively. It was discovered for the first time that, photosynthesis rates also play a significant role in the accumulation of secondary metabolites. Photosynthesis rates between 0.39 μmol CO2/m2s and 1.21 μmol CO2/m2s over three weeks were crucial for the optimal accumulation of phenolic acids such as caffeic acid derivates, coumaric acid hexoside, ferulic acid hexoside and coumaroylquinic acids as well as for quercetin and flavonoid. An optimal temperature range between 20.94 and 21.53°C and a PPFD from 250.0 to 375.2 μmol/m2s was classified as beneficial to synthesize these compounds. Optimal light intensity for the total phenolic acids (129.35 - 274.34 μmol/m2s) and for the total flavonoids (31.24 - 249.31 μmol/m2s), the optimum relative humidity levels are between 83.45 - 91.29% and 87.13 - 91.29%, respectively. Based on these results, this study provides the first evidence that the impact of a single climate factor on secondary metabolites in tomato fruits should not be considered in isolation, but rather, all climatic factors during a growth period must be taken into account to predict the optimal accumulation of individual phenolic compounds and carotenoids in tomatoes. Our results have laid the headstone to help growers target their climate controls to maximize the health-promoting phytochemicals in tomatoes.